Theoretical Study of Non-additive Hard Convex Body Fluid Mixtures - Dey, Tarun Kumar (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2017)
The structure of a dense fluid or liquid is largely determined by the repulsive intermolecular forces, so the hard core potential has been extensively employed to model real fluids and fluid mixtures. The properties of two dimensional hard body fluids and fluids mixtures have aroused a considerably interest in recent years. This is because they are treated as models of real fluids or fluid mixtures absorbed onto surfaces. The 2D hard-body fluids and fluid mixtures like their three-dimensional counter part are useful reference system in framing a perturbation theory for 2D real fluids and fluid mixtures of non-spherical molecules. The 2D hard-body systems are convex body (HCB) systems such as ellipse (HE) and hard discorectangles (HDR) and hard non-convex body systems i.e., fused hard discs (FHD) and planar hard dumbbell (HDB) systems. The equation of state of hard convex body fluid mixtures (HCB) is studied. Analytic expressions are given for the equation of state of the fluid mixture of the non-additive HCB. The numerical results are discussed for the non-additive hard dumbbell (HDB) fluid mixtures under different conditions for different values of non-additivity \(Δ\). They depend on the conditions, shape parameters \(L^*_11\) and \(L^*_22\) , mole fractions \(x_1\) and \(x_2\) and \(Δ\) in general and increase with the increase of packing fraction \(Δ\).